16. EFEKTIVITAS SEATCA DALAM PENANGANAN PERDAGANGAN ROKOK ILEGAL DI MALAYSIA TAHUN 2010 - 2012 - Fitriasari, Fransiska Alfiana; Putranti, Ika Riswanti; Puspapertiwi, Sheiffi (Journal of International Relations, 2016)
Tobacco issue has become world’s attention in 1990. The issues that arise due to tobaccoconsumption become the background of international tobacco control regimes establishment,called Framework Convention on Tobacco Control, in 2005. In 2001, a tobacco controlalliance also established in Southeast Asia, it is called Southeast Asia Tobacco ControlAlliance. Malaysia is a country that faces high illegal cigarette trade, they are kreteksmuggling and illicit white. Illegal cigarette trade has harmed Malaysia in social, economy,and health. After the establishment of Framework Convention on Tobacco Control, SoutheastAsia Tobacco Control Alliance has a function as the main pillar of tobacco control inSoutheast Asia. Southeast Asia Tobacco Control Alliance has a duty as an implementationcatalyst of the Framework Convention on Tobacco Control in Southeast Asia. Southeast AsiaTobacco Control Alliance encourages the Southeast Asian countries to make policies inaccordance with the Framework Convention on Tobacco Control and to overcome all theexisting tobacco issues to achieve the common goal. The purpose of this study are to identifyand explain the effectiveness of Southeast Asia Tobacco Control Alliance in handling illegalcigarette trade in Malaysia in 2010-2012. The type of this research is explanative. This studyis analyzed by using qualitative data analysis techniques and theory of international regimes.The result of the research shows that Southeast Asia Tobacco Control Alliance as the mainpillar of tobacco control in Southeast Asia is not effective in handling illegal cigarettes inMalaysia in 2010-2012.